Analisis Deskripsi Pekerjaan, Rekrutmen, dan Beban Kerja terhadap Kinerja Pegawai di Kantor Badan Riset dan Inovasi Daerah (BRIDA) Kota Medan - Nur Ainun Damanik; Husni Muharram Ritonga (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study was conducted at the Brida Office in Medan City to determine how job descriptions, recruitment, and workload affect employee performance in carrying out their duties and responsibilities. The population consisted of 42 permanent employees working at the Brida Medan office, and the sample was taken with saturated sampling, totaling 42 respondents. Primary and secondary data were used, and collected through literature studies, surveys, and observations. Data analysis used multiple linear regression, classical assumption tests, and hypothesis tests. The results showed that job descriptions, recruitment, and workload had a positive and significant effect on employee performance partially and simultaneously. At the Brida Medan office, there was a strong correlation between employee performance in completing tasks and job descriptions, and workload. Employee performance at the Brida Medan office can be explained by job descriptions, recruitment and workload by 53.1% and the remaining 46.9% can be explained by other variables not studied.